Anti-inflammatory Effects of Heme Oxygenase-1 Depend on Adenosine A2A- and A2B-Receptor Signaling in Acute Pulmonary Inflammation - Konrad, Franziska M.; Zwergel, Constantin; Ngamsri, Kristian-Christos; Reutershan, Jörg (Frontiers in Immunology, 2017)
Acute pulmonary inflammation is still a frightening complication in intensive care units. In our previous study, we determined that heme oxygenase (HO)-1 had anti-inflammatory effects in pulmonary inflammation. Recent literature has emphasized a link between HO-1 and the nucleotide adenosine. Since adenosine A2A- and A2B-receptors play a pivotal role in pulmonary inflammation, we investigated their link to the enzyme HO-1. In a murine model of pulmonary inflammation, the activation of HO-1 by hemin significantly decreased polymorphonuclear leukocyte (PMN) migration into the lung. This anti-inflammatory reduction of PMN migration was abolished in A2A- and A2B-knockout mice. Administration of hemin significantly reduced chemokine levels in the BAL of wild type animals but had no effects in A2A-/- and A2B-/- mice. Microvascular permeability was significantly attenuated in HO-1-stimulated wild type mice, but not in A2A-/- and A2B-/- mice. The activity of HO-1 rose after LPS inhalation in wild type animals and, surprisingly, also in A2A-/- and A2B-/- mice after the additional administration of hemin. Immunofluorescence images of animals revealed alveolar macrophages to be the major source of HO-1 activity in both knockout strains – in contrast to wild type animals, where HO- 1 was also significantly augmented in the lung tissue. In vitro studies on PMN migration further confirmed our in vivo findings. In conclusion, we linked the anti-inflammatory effects of HO-1 to functional A2A/A2B- receptor signaling under conditions of pulmonary inflammation. Our findings may explain why targeting HO-1 in acute pulmonary inflammation has failed to prove effective in some patients, since septic patients have altered adenosine receptor expression.